TRACKING THE LINKAGE BETWEEN MIGRATION AND GLOBAL TERRORISM IN HANDLING OF IRREGULAR TRANSNATIONAL MOVEMENTS - Rohmad Adi Yulianto (VERITAS, 2016)
The movement of peoples in today’s refugees problems is more complicated than thephenomena of refugees in pre 21st century or the era of world war I and II, which wereland borders and identities unified by the terms of nation-state, defining the citizens andaliens through the solid model of nationality. In contemporary refugees discourse, theproblems of unwanted forced migration not only covering the protection of people bysupplying their standard of living as an effect of displacement peoples living out of theircountries, but also facing new variables of problem, including economic and ideologicalfactors that became their motives of migration. More than half of all current refugees in theworld come from many states of Muslim countries as a consequence of war and conflictsthat still lasted for more than decades. The conception of Ummah in Islam doctrine ofsociety encourage all Muslims in the world to take a part of responsibility sharing theburden Muslims refugees condition, including receiving them to live and survive inside thestructure of society based on same faith and equal status before Allah the Creator, but inmany cases, this policy contradicted to the concept of nationality which based on nationstateconception of identity and state sovereignty. Indonesia, country with largest Muslimpopulation in the world, has received mass influx of Muslim refugees during the recentyears.